2014
DOI: 10.4067/s0718-95162014005000072
|View full text |Cite
|
Sign up to set email alerts
|

Use of biochar on two volcanic soils: effects on soil properties and barley yield

Abstract: The use of biochar in agricultural soils appears to be promising because it is known to improve soil properties and increase crop production. However, few studies have been conducted with biochar on volcanic soils. Two field experiments were conducted simultaneously to evaluate the effect of oat hull biochar (OBC) on various physical-chemical properties of two volcanic soils, an 'Inceptisol' and an 'Ultisol', and to evaluate the resulting effects on the yields of barley (Hordeum vulgare) grown on these soils. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
(40 reference statements)
2
21
1
Order By: Relevance
“…Qayyum et al (2014) and Kloss et al (2014) found a much higher increase in soil organic carbon content after biochar application, whereas in the study by Curaqueo et al (2014) and Abrishamkesh et al (2015) this content was found to be lower. The distinct increase in carbon content in the third year of the experiment, especially in the treatments with biochar addition at the rates of 20 and 30 t/ha is difficult to explain.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Qayyum et al (2014) and Kloss et al (2014) found a much higher increase in soil organic carbon content after biochar application, whereas in the study by Curaqueo et al (2014) and Abrishamkesh et al (2015) this content was found to be lower. The distinct increase in carbon content in the third year of the experiment, especially in the treatments with biochar addition at the rates of 20 and 30 t/ha is difficult to explain.…”
Section: Resultsmentioning
confidence: 61%
“…The obtained results are evidence of the complexity of the processes taking place in the soil as affected by the biochar rates applied. After biochar application, Curaqueo et al (2014), Břendová et al (2015) and Gul et al (2015) also found an increase in soil pH. In turn, Kloss et al (2015) found a decrease in soil pH after 7 months from incorporation of straw-derived biochar.…”
Section: Resultsmentioning
confidence: 88%
“…In some cases, soils with organic C concentrations as low as 0.43% may not exhibit any changes in wet aggregate stability after biochar application (Dong et al, 2016). On the other hand, soils with organic C concentrations as high as 10% on a grassland in New Zealand (Herath et al (2013) and 4.5% on a volcanic soil in Chile (Curaqueo et al, 2014) exhibited greater soil aggregate stability than the controls after biochar addition.…”
Section: Biochar and Soil Structural Properties Wet Aggregate Stabilitymentioning
confidence: 99%
“…Biochar improves physical properties of soil, such as water holding capacity and soil aggregation (Obia et al, 2016;Curaqueo et al, 2014). It also recovers soil chemical properties such it increases the soil cation exchange capacity (Mohamed et al, 2016), thus increases nutrients against leaching and makes some of them more available to plants e.g., N, P and K (Amin, 2016;Gao et al, 2016;Muhammad et al, 2016;Shen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%